2023
DOI: 10.1590/fst.116022
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum accumulation in the wheat production chain: a review

Abstract: The consumption of food containing significant amounts of aluminum has been the focus of discussions related to health. Aluminum is distributed in nature and may be naturally present in raw materials or added to food as a result of activities or modification processes along the food production chain. This exploratory and descriptive research identified possible sources of aluminum in food, in general, and particularly in the wheat chain and its derivatives, which comprise an important class in the food chain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
0
0
Order By: Relevance
“…Understanding the genes involved in aluminum accumulation and its impact on the plant can help to develop strategies to mitigate its harmful effects and improve the overall yield and quality of durum wheat crops. As durum wheat is a staple food in many regions, especially in Türkiye and meditation countries, high levels of aluminum in food can pose a risk to human health (Agency for Toxic Substances and Disease Registry-ATSDR., 2008; Mello et al, 2023), therefore, it is crucial to develop methods to reduce aluminum accumulation in durum wheat to ensure food safety and promote human health like using molecular markers for GWAS. Microsatellites have been previously recognized as effective markers in GWAS due to their ability to cover a wider genomic region and offer several advantages, including higher resolution, greater inter-population variability, and significant intrinsic applicability (Alsaleh, 2022c;Väli et al, 2008).…”
Section: Exploring Genetic Variations and Associations With Markers A...mentioning
confidence: 99%
See 4 more Smart Citations
“…Understanding the genes involved in aluminum accumulation and its impact on the plant can help to develop strategies to mitigate its harmful effects and improve the overall yield and quality of durum wheat crops. As durum wheat is a staple food in many regions, especially in Türkiye and meditation countries, high levels of aluminum in food can pose a risk to human health (Agency for Toxic Substances and Disease Registry-ATSDR., 2008; Mello et al, 2023), therefore, it is crucial to develop methods to reduce aluminum accumulation in durum wheat to ensure food safety and promote human health like using molecular markers for GWAS. Microsatellites have been previously recognized as effective markers in GWAS due to their ability to cover a wider genomic region and offer several advantages, including higher resolution, greater inter-population variability, and significant intrinsic applicability (Alsaleh, 2022c;Väli et al, 2008).…”
Section: Exploring Genetic Variations and Associations With Markers A...mentioning
confidence: 99%
“…According to Mulugeta et al (2023), Canada and Türkiye are the largest producers of Durum wheat. However, Triticum turgidum has a genetic propensity to accumulate elements from the soil in its grains, which can exceed international safety standards as indicated by Delhaize et al (2012), Garcia-Oliveira et al (2016), and Liu et al (2018) and they reported that genetic factors play a significant role in the extent of aluminum accumulation in the grains of various durum wheat cultivars (Mello et al, 2023). Aluminum (Al) is a common element in the earth's crust and is often found in high concentrations in acidic soils (Mello et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations